1997
DOI: 10.1254/jjp.60.357
|View full text |Cite
|
Sign up to set email alerts
|

High Affinity Binding of Azasetron Hydrochloride to 5-Hydroxytryptamine3 Receptors in the Small Intestine of Rats

Abstract: -Monkey cerebral artery strips partially contracted with prostaglandin F2a responded to histamine with biphasic patterns of relaxation. The delayed and sustained relaxation was suppressed by cimetidine, whereas the phasic response was abolished by treatment with chlorpheniramine and NG nitro-L-arginine (L-NA), a nitric oxide (NO) synthase inhibitor. The inhibition by L-NA was reversed by L-arginine. D-NA was without effect. Endothelium denudation abolished the phasic relaxation. We hypothesized that endotheliu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 38 publications
1
22
0
Order By: Relevance
“…We used ADP, acetylcholine and nitroglycerin to examine eNOS-dependent and -independent reactivity of cerebral arterioles in nondiabetic and diabetic rats. We and others (Ayajiki et al, 1992;Faraci, 1991;Mayhan, 1992b) have shown that ADP and acetylcholine, but not nitroglycerin, dilate cerebral arterioles via the synthesis/release of nitric oxide. Other investigators You et al, 1999), however, have suggested that relaxation of the rat middle cerebral artery to purines is related to the synthesis/release of nitric oxide and EDHF.…”
Section: Consideration Of Methodsmentioning
confidence: 80%
“…We used ADP, acetylcholine and nitroglycerin to examine eNOS-dependent and -independent reactivity of cerebral arterioles in nondiabetic and diabetic rats. We and others (Ayajiki et al, 1992;Faraci, 1991;Mayhan, 1992b) have shown that ADP and acetylcholine, but not nitroglycerin, dilate cerebral arterioles via the synthesis/release of nitric oxide. Other investigators You et al, 1999), however, have suggested that relaxation of the rat middle cerebral artery to purines is related to the synthesis/release of nitric oxide and EDHF.…”
Section: Consideration Of Methodsmentioning
confidence: 80%
“…ADP appears to dilate cerebral arterioles via the activation of NOS, presumably eNOS (3,15,30). However, some have suggested that relaxation of the rat middle cerebral artery to purines is related, in part, to the synthesis/release of nitric oxide and to Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Pathophysiological conditions such as vascular dilation [40], hyperemia [16,41], hypotension [42] and migraine [43] were reported to be mediated via the H 1 [15] or H 2 [16] receptor stimulated formation of NO. Inhibition of the endogenous and inducible nitric oxide synthase during histamine stimulation with a highly potent competitive inhibitor lead to a concentration dependent significant decrease of PMN adhesion within the first 30 min of stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Nitric oxide plays an important role in inflammatory responses and has also been proposed to be involved in the biochemical signaling pathway of histamine. Histamine stimulated synthesis of nitric oxide [14], can be mediated via the H 1 receptor [15] or the H 2 receptor [16], depending on the tissue and species under investigation.…”
Section: Introductionmentioning
confidence: 99%